Classificação topológica de sistemas de controle lineares - Bruno Alexandre Rodrigues (2015)
In this work we study the problem of classification of linear control systems. We do this first by using families of trajectories associated to a control system and after we use skew product flows to obtain another kind of classification. As main goal, we will state that two control systems are topologically conjugate if, and only if, they have the same Kronecker indices, the same inertia and the matrices that generate the noncontrollable parts of the systems are similar. We also show that if the control range is compact, then to a control system of the form